Analysis and design of ultra‐wideband low noise amplifier using complementary structure with series inductive peaking technique and shunt feedback. (27th April 2021) - Kazemi, Amir Hossein; Hayati, Mohsen
Summary: In this paper, an ultra‐wideband low noise amplifier (LNA) is presented using 0.18‐μm RF CMOS technology. A complementary structure with series inductive peaking technique is introduced by using two inductor‐loops to achieve flat gain. In the first and third stages, two complementary structures are utilized to achieve a high and flat gain, a wideband input impedance matching and a low noise figure. In addition, a shunt feedback is utilized to increase input impedance matching and stability. In the second stage, a common source structure is used as interstage, which increases the −3 dB bandwidth. The designed LNA presents a high and flat gain of 15.6–16.5 dB, an excellent input return loss better than −11 dB and a good NF of 2.2–3 dB in the frequency range of 3.1–10.6 GHz. Also, the proposed structure consumes 6.8 mW from a 0.8‐V supply voltage and has an IIP3 of −4 dBm at 6.5 GHz. The proposed structure only occupies 0.59 mm 2 . Abstract : In the proposed LNA, a modified complementary structure is introduced by using two inductor‐loops to achieve flat gain. In the first and third stages, two modified complementary structures are used to achieve a high and flat gain, a wideband input matching, and a low noise figure. Also, a shunt feedback is utilized to increase input matching and stability. In the second stage, a common source structure is used to increase the bandwidth. This topology results in good characteristics.